The victorian readers of Wilkie Collins - Silva, Ana Carolina (Revista de História, 2024)
The aim of this paper is to examine the relations between the British writer Wilkie Collins (1824-1889) and his Victorian readers. By indicating the profile of Collins’ readers, this investigation seeks to analyze not only the reading practices current in the British society of the middle of the nineteenth century, but also to delineate the conditions and the dynamics of production, circulation and reception of the Victorian novels published in the periodicals. Thus, it is an exercise that thinks the fictional writing beyond the internal protocols of the literary text, by trying not to lose track of and bring to the investigative plan the importance of the materiality of textual supports during the process of the construction of the narrative and its meanings. It is via the triangulation between writing, publication norms and reading experiences that the paths of history and literature cross in this study.